Penyalahgunaan Kuasa Imamat Dalam Kasus Sexual Abuse - Martinus Renda; Ronalius Bilung; Yoseph Kabalesy; Johanes Hegemur; Edison R. L. Tinambunan (Studia Philosophica et Theologica, 2022)
Abstract This study focuses on the actions of the priesthood by priests related to the prevalence of sexual abuse cases among the clergy. The disgraceful acts committed by the priests have become a disgrace that the Church has to endure to this day. The church as a continuation of Christ's mission in the world feels the need to reorganize and reorganize by taking a firm stance in resolving the current struggle. To maintain her holiness, the Church first takes a stance of refusing and will not allow the clergy to continue to create sin in her body. Through its leaders, the Church continues to seek to voice that priests should take the path of repentance and return to the essence of priestly life which has united it with the priesthood of Christ. In addition, the Church lovingly welcomes and accepts those who have been victims of sexual abuse by priests. The Church hopes that they will continue to love the Church and believe that the Church is a home that protects and protects them from all crimes and inhumane treatment. As a form of feeling, the Church will continue to stand for justice and respect the rights and dignity of life for victims of sexual harassment, providing assistance, assistance, and healing service to rediscover the meaning of life that is valuable and worthy. Keywords: priesthood power, sexual harassment, ministerial priesthood, pastoral. Abstrak Studi ini menaruh perhatian pada tindakan penyalahgunaan kuasa imamat yang dilakukan oleh para imam terkait dengan merebaknya kasus sexual abuse dikalangan kaum klerus. Tindakan tidak terpuji yang dilakukan oleh para imam telah menjadi aib yang harus ditanggung oleh Gereja hingga saat ini. Gereja sebagai kelanjutan dari misi Kristus di tengah dunia merasa perlu untuk membenah dan menata dirinya kembali dengan mengambil suatu sikap tegas dalam menyelesaikan pergulatan yang tengah terjadi. Demi menjaga kekudusannya, Gereja pertama-tama mengambil suatu sikap untuk menolak dan tidak akan pernah membiarkan kaum klerus terus menerus menciptakan dosa di dalam tubuhnya. Melalui para pemimpinnya Gereja terus berupaya menyuarakan agar para imam mengambil jalan tobat dan kembali kepada hakikat hidup imamat yang telah mempersatukannya dengan imamat Kristus. Di samping itu Gereja dengan penuh cinta menyambut dan menerima mereka yang telah menjadi korban sexual abuse yang dilakukan oleh para imam. Gereja berharap mereka tetap mencintai Gereja dan percaya bahwa Gereja menjadi rumah yang akan menjaga dan melindungi mereka dari segala kejahatan dan perlakuan yang tidak berprikemanusiaan. Sebagai bentuk rasa tanggungjawabnya, Gereja akan terus berdiri di atas keadilan dan menghormati hak serta martabat hidup para korban sexual abuse, memberikan pendampingan, pertolongan serta tindakan penyembuhan sehingga menemukan kembali makna hidup yang berharga dan bernilai. Kata kunci: kuasa imamat, sexual abuse, imamat ministerial, pastoral.